Investing in African Livestock : Business Opportunities in 2030-2050 - Pica-Ciamarra Ugo (World Bank, Washington, DC, 2014)
Medium and long-term development perspectives of any productive sector are driven by prospects for demand growth which, dependent on the policy and economic environment, can translate into associated producer responses. For the livestock sector, trends in the consumption of animal-sourced foods and livestock by-products are the first key indicator of opportunities for investment. This paper depicts the medium to long term development prospects for the African livestock sector by reviewing data on the estimated consumption of animal-sourced foods and anticipated responses by producers for 2005-07, 2030, and 2050. By 2050, the meat market is projected at 34.8 million tones and that of milk about 82.6 million tones, an increase of 145 and 155 percent respectively over 2005-07 levels. More notably, over this period, Africa's increase in volume of meat consumed will be on a par with that of the developed world and that of Latin America, with only South Asia and Southeast Asia anticipated registering higher growth. Policy and institutional reforms should be devised, building on solid data and evidence based analysis, to ensure that the business opportunities generated by the growing market for animal-sourced foods translate into widespread benefits for the populace, including livestock producers, and for other actors along the value chains as well as consumers. This report reviews African trends in the consumption of livestock products compared to other major world's regions, as well as positioning these trends within the evolving trade position of the African continent.